The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fchem.2019.00196
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Various 2-Hydroxyethylammonium Sulfonate -Based Protic Ionic Liquids and Their Potential Application in Hydrodeoxygenation

Abstract: In order to obtain the regularities of physicochemical properties of hydroxy protic ionic liquids (PILs) and broaden their potential application, a series of 2-hydroxyethylammonium sulfonate-based PILs were synthesized through proton transfer reaction and characterized by NMR and FT-IR and elemental analysis. Their phase transfer behavior ( T m ) and initial decomposition point ( T d ) were characterized by differential scanning calorimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…According to Keshapolla et al and Bandres et al, the relationship between high thermal stability and long alkyl chain attached to the ionic liquid could be attributed to the presence of strong intermolecular and intramolecular forces in the alkyl chain [ 41 , 42 ]. In addition, it was observed that the T d values of PILs with a common cation are relatively close to one another and a similar observation was recorded by Cai et al, involving a series of ionic liquids namely triethanolamine methanesulfonate [TEA][mesy], triethanolamine trifluoromethanesulfonate [TEA][OTf] and triethanolamine benzenesulfonate [TEA][Bsa] [ 43 ]. On the other hand, the thermal stability of the ammonium-based PILs synthesized in this work is relatively low when compared to other types of ionic liquids.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…According to Keshapolla et al and Bandres et al, the relationship between high thermal stability and long alkyl chain attached to the ionic liquid could be attributed to the presence of strong intermolecular and intramolecular forces in the alkyl chain [ 41 , 42 ]. In addition, it was observed that the T d values of PILs with a common cation are relatively close to one another and a similar observation was recorded by Cai et al, involving a series of ionic liquids namely triethanolamine methanesulfonate [TEA][mesy], triethanolamine trifluoromethanesulfonate [TEA][OTf] and triethanolamine benzenesulfonate [TEA][Bsa] [ 43 ]. On the other hand, the thermal stability of the ammonium-based PILs synthesized in this work is relatively low when compared to other types of ionic liquids.…”
Section: Resultssupporting
confidence: 70%
“…Primarily, the T m of PIL is dependent on the crystal lattice strength in the PIL. The low T m of the PIL could be related to the low crystal lattice energy due to poor packing efficiency in the crystal lattice of PIL itself [ 43 , 49 ]. The data obtained in this work suggests that [BEHA][C7] has a better packing of the counterions in its structure than that of [BEHA][C5] and [BEHA][C6].…”
Section: Resultsmentioning
confidence: 99%
“…156 Furthermore, MEA-MSA has been reported to have properties of a protic ionic liquid, even though it remains a solid at room temperature. [156][157][158][159] Its properties include a glass transition of À44 1C, melting point of about 100 1C, and a thermal stability up to 286-323 1C for the fused salt. 156 Tropospheric air contains significant amounts of water vapor, hence the impact of relative humidity (RH) on particle formation from MEA + MSA was also examined.…”
Section: Resultsmentioning
confidence: 99%
“…156 Furthermore, MEA–MSA has been reported to have properties of a protic ionic liquid, even though it remains a solid at room temperature. 156–159 Its properties include a glass transition of −44 °C, melting point of about 100 °C, and a thermal stability up to 286–323 °C for the fused salt. 156…”
Section: Resultsmentioning
confidence: 99%
“…PIL’s with hydroxy cation are more popular, as it can form strong hydrogen bonds between PIL and variety of other compounds resulting in increased miscibility. 74 Halogen-free protic ionic liquids are proved to be less destructive to the environment and more compatible with bio-based lubricants. 75…”
Section: Introductionmentioning
confidence: 99%